Aditivos alimentares em biscoitos, bebidas lácteas e iogurtes comercializados em supermercados - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Additives play important roles in the food industry, contributing to improving the quality and safety of ultra-processed products. However, due to excessive consumption of these additives, there may be risks of chronic non-communicable diseases. The objective was to characterize the food additives present in industrialized biscuits, dairy drinks and yogurts sold in supermarkets in a city in the interior of Rio Grande do Sul. The ingredient lists of 174 products in supermarkets were photographed. The information was tabulated in Excel, the additives were characterized and then descriptive statistical analysis was performed. Analysis of variance (ANOVA) was used to evaluate the differences in additive means between cookies and yogurts and cookies and dairy drinks. A total average of 6.10 additives was found in the entire sample, being more prevalent in dairy drinks. The most frequently found were sweeteners, followed by thickeners and stabilizers, with sweeteners being the most prevalent in the entire sample. The number of additives was significantly higher among dairy drinks when compared to cookies and among yogurts when compared to cookies. It is concluded that there is a prevalence of additives in industrialized products, dairy drinks stood out with the highest average number of additives. Stabilizers, colorings and sweeteners were the additives with the highest averages across the entire sample. The results show the importance of understanding and raising awareness about the presence of food additives in processed foods, due to the risk they cause to health when consumed in the long term, helping consumers to make good food choices.
Food additives in cookies, dairy drinks and yogurts sold in supermarkets
Keywords: Ultraprocessados; Edulcorantes; Industrializados; Ultra-processed; Sweeteners; Industrialized; CIENCIAS DA SAUDE